Transformasi Digital dan Karakteristik Wirausaha sebagai Solusi dalam Meningkatkan Kinerja UMKM Kuliner di Kota Bandung - Salsa Satriani Setiawan; Suryana Suryana; Heny Hendrayati (Pusat Riset dan Inovasi Nasional, 2025)
The culinary business has grown fast in the age of globalization and digitalization. However, despite this expansion, culinary MSMEs confront a number of obstacles, including a decrease in the number of firms and revenues, which has a negative influence on overall business performance. This study seeks to investigate the impact of digital transformation and entrepreneurial characteristics on the performance of culinary MSMEs in Bandung. The study uses a descriptive and verification quantitative approach using a saturated sampling technique. The unit of analysis in this study is culinary MSME actors, with a total sample of 100 respondents. Classical assumption testing and multiple regression analysis are among the data analysis techniques. The findings show that digital transformation and entrepreneurial characteristics have a favorable and considerable impact on business success, both concurrently and partially. These findings suggest that applying digital transformation and boosting entrepreneurial characteristics are crucial factors in enhancing the performance of culinary MSMEs.